2018
DOI: 10.29121/granthaalayah.v6.i9.2018.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon Application Ontaliouine Crocus Sativus (L) Cultivation Undersalt Stress

Abstract: This study investigates the effect of silicon (Si) application on saffron plantgrown under salt stress. Therefore; Saffron, Crocus sativus L. was grown in different treatments of NaCl in presence and absence of 1 mM of silicon in its soluble form, orthosilicic acid(H4SiO4). Our results exhibited that the application of silicon enhanced the physiologicalstudied parameters and morphological attributes of saffron stigmas; the length of stigma improvement was 29% and 41,4% in saline treatments of 50 mM and 100mM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…We observed a significant negative effect of K 2 SiO 3 addition on leaf carotenoid and anthocyanin contents in the well-watered plants, while the contents of these pigments increased with K 2 SiO 3 addition in the water-deprived plants. The latter response is in line with the study from Jamila et al [53], who reported about higher chlorophyll and carotenoid contents in Si-enriched and salt-stressed Coriandrum sativum. These differences are possibly due to the multiple effects of Si, such as the amelioration of plant water content and photosynthetic activity, and the reduction in oxidative stress [54].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a significant negative effect of K 2 SiO 3 addition on leaf carotenoid and anthocyanin contents in the well-watered plants, while the contents of these pigments increased with K 2 SiO 3 addition in the water-deprived plants. The latter response is in line with the study from Jamila et al [53], who reported about higher chlorophyll and carotenoid contents in Si-enriched and salt-stressed Coriandrum sativum. These differences are possibly due to the multiple effects of Si, such as the amelioration of plant water content and photosynthetic activity, and the reduction in oxidative stress [54].…”
Section: Discussionsupporting
confidence: 92%
“…Electrolyte leakage indicates damage caused to cell membranes and is an important parameter for evaluating plant oxidative stress. Regarding salinity conditions, increased leakage has already been verified for crops such as coriander (Jamila et al, 2019), cherry tomato (Batista et al, 2021), and lettuce, where a 61% higher rate of electrolytes leakage was mentioned in plants by saline stress (40 mM NaCl) than control treatment (Freitas et al, 2019).…”
Section: Continued On the Next Pagementioning
confidence: 84%